Vitality, fermentation, aroma profile, and digestive tolerance of the newly selected Lactiplantibacillus plantarum and Lacticaseibacillus paracasei in fermented apple juice - Liang, Jia Rui; Deng, Hong; Hu, Ching Yuan; Zhao, Peng Tao; Meng, Yong Hong (Frontiers in Nutrition, 2022)
To enrich the probiotic lactic acid bacteria (LAB) strains and expand the commercialization of new fermented juice products, we have identified two LAB strains with excellent potential in fermenting apple juice from pickles. The two strains were morphologically, physiologically, and genetically characterized and identified as Lacticaseibacillus paracasei (WFC 414) and Lactiplantibacillus plantarum (WFC 502). The strains’ fermentation performance and alterations in volatile aroma components of apple juice and ability to survive in a simulated gastrointestinal environment were evaluated. The growth of WFC 414 and WFC 502 in apple juice for 48 h reached 8.81 and 9.33 log CFU/mL, respectively. Furthermore, 92% and 95% survival rates were achieved in 2 h simulated gastric juice, and 80.7% and 83.6% survival rates in 4 h simulated intestinal juice. During the fermentation, WFC 414 and WFC 502 reduced the soluble sugars and total polyphenols in apple juice, and consumed malic acid to produce large amounts of lactic acid (3.48 and 5.94 mg/mL). In addition, the esters and aldehydes were reduced, and the production of alcohols, acids and ketones was elevated in the apple juice fermented by both strains. These results show that WFC 414 and WFC 502 have great potential applications in the fermented fruit juice industry.